Transitional Care for Improving Health Care Quality in Hospital: A Literature Review - Iriawandani, Debie Saktyana; Ardiana, Anisah; Rondhianto, Rondhianto (Indonesian Journal of Global Health Research, 2024)
The transition of care from hospital to home is a critical period for patients, especially those with chronic conditions such as heart failure. During the transition period, patients often experience difficulties managing their disease, which can lead to an increased risk of rehospitalization. This literature review aims to analyze scientific evidence about the effectiveness of transitional care interventions in improving the quality of health care in hospitals, especially for patients with chronic conditions. The method of this study is a literature review. This study used electronic databases such as PubMed, ScienceDirect and Google Scholar. The selected articles are quantitative research articles published within the last 5 years available in full text and not the result of a review. The results of the review show that transitional care interventions have a significant positive impact on the quality of health care. This intervention can increase self-management, treatment adherence and patient satisfaction with heart failure. Some components of effective interventions include patient education, care coordination, outpatient follow up and social support. Transitional care interventions are an effective strategy to improve the quality of health care, especially in patients with chronic conditions. The implementation of a comprehensive transitional care program in hospitals needs to continue to be improved to achieve optimal results.